Residual Effect of Deltamethrin Insecticide at Rice Plants Against the Parasitism Level of Anagrus Nilaparvatae Parasitoids (Hymenoptera: Mymaridae) - Meilin, Araz; Trisyono, Y. Andi; Buchori, Damayanti (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
The impact of deltamethrin on natural enemies can be determined directly through contact and oral applications or indirectly through residues on plants. This research was aimed to determine the indirect impact of deltamethrin on the egg parasitoid of Anagrus nilaparvatae.Â  The rice plants of Cisadane variety were infested with 10 gravid females of N. lugens. Deltamethrin was applied at two concentrations (12.5 and 6.25 ppm) and at 7, 3, 1 day and 3 hours before the parasitization. Deltamethrin residues on rice plants were decrease the number of Nilaparvata lugens, parasitoid andÂ  parasitization level of A. nilaparvatae. This suggests that deltamethrin residue on rice plants could decrease the role of A. nilaparvatae in controlling N. lugens.